Operator Approach in Solving the Problem of Small Motions of a System of Ideal Capillary Fluids (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2019)
الهدف من هذا البحث هو دراسة وتعميم بعض النتائج المتعلقة بمسألة الحركات الصغيرة لنواس ذي تجويف مملوء بسائل شعري مثالي واحد  إلى مسألة الحركات الصغيرة لنواس ذي تجويف مملوء بمجموعة من السوائل الشعرية المثالية. في بداية البحث نقوم بعرض المسألة، ثم نحول المسألة الحدية الابتدائية لهذه المسألة إلى معادلة تفاضلية من المرتبة الثانية في فضاء هلبرت ونبرهن نظرية حول وجود حل قوي وحيد لهذه المعادلة، والطريقة المعتمدة هي من الطرائق الهامة والحديثة في دراسة مسائل الجمل الهيدروديناميكية. The aim of this paper is to study and generalize some results concerning the problem of small motion of a pendulum with a cavity filled with an ideal capillary fluid [4] to the problem of small motions of a pendulum with a cavity filled with a system of ideal capillary fluids. At the beginning of the paper, we present the problem; then, we transform its initial boundary-value problem to a differential equation of second order in the Hilbert space. Yet, we prove a theorem to have a unique strong solution for this equation. The applied method is an important and new one in studying the problems of hydro-dynamical systems.